ADCP water/ice velocity relative to ROV from ROV survey PS122/3_31-75 on 2020-03-14, survey 1 - Anhaus, Philipp; Katlein, Christian; Matero, Ilkka; Nicolaus, Marcel; Arndt, Stefanie; Krampe, Daniela; Lange, Benjamin Allen; Regnery, Julia; Rohde, Jan; Schiller, Martin (In: Anhaus, Philipp; Katlein, Christian; Matero, Ilkka; Nicolaus, Marcel; Arndt, Stefanie; Krampe, Daniela; Lange, Benjamin Allen; Regnery, Julia; Rohde, Jan; Schiller, Martin (2023): Water/ice velocity from remotely operated vehicle (ROV) surveys during the MOSAiC expedition 2019/20 [dataset publication series]. PANGAEA, https://doi.org/10.1594/PANGAEA.953510, 2023)
Water/ice velocity relative to the remotely operated vehicle (ROV) has been regularly measured by a Nortek Aquadopp Profiler 2MHz acoustic doppler current profiler (ADCP) during the MOSAiC expedition 2019/20.
Keywords: ADCP; BEAST; MOSAiC expedition; Remotely operated vehicle (ROV); Sea ice